Evolution of adrenalectomized patients for advanced breast cancer - Priario, Julio César; Gateño Yaffe, Nisso; Borges, Freddy; Favat, Juan; Ramos, Sergio; D'Auria, Agustín (Cirugía del Uruguay, 1972)
Twenty-six cases of bilateral adrenalectomy performed in the treatment of advanced breast cancer, are presented. Results obtained are analyzed according to the different locations, and the rate of survival is studied. In more than one third of all cases, improvent resulted.